Avaliação do conhecimento e atitudes dos profissionais de saúde de um hospital de ensino sobre proteção radiológica - Batista, Vinicius Martins Dias (2017)
Background: The concept of radioprotection is usually recognized as important among the technical level of health professionals and higher. However, the information on the formal knowledge and its application in practice are scarce. Noticing the discrepancy in radiation protection process in sectors using ionizing radiation, decided to search the knowledge that health professionals have on radiation protection and the need for educational intervention for professionals to work consciously and with adequate protection. Objectives: To assess the knowledge that the health professionals of a university hospital (UH) have about radioprotection, educate staff about the harmful effects of ionizing radiation and application of the ALARA (As Low As Reasonably Achievable) principle in routine work and implement the knowledge of radioprotection through playful learning using teaching materials and easy to understand. Methods: This is an exploratory cross-sectional study with a qualitative analysis of the open questions and the quantitative issues addressed by a semi-structured questionnaire was applied to 59 employees from different sectors of UH to assess the degree of knowledge. From the findings it was prepared a booklet with playful images to be distributed to all employees of the UH. In the internal prevention week of work accidents at the UH it was made by the employees a performance about radioprotection. Results: According to the participants with technical or graduated degree, they did not have training on radiation protection as students or it was insufficient to practice. The work environment, even in a UH, provides little information about radiation protection and the rules which govern it. Much of the respondents (25%) even knowing not observe the radiation protection procedures. In the assessment of formal knowledge on the concept and the usual measures of radioprotection we observed that 1/3 of the participants have good theoretical knowledge, 1/3 have incomplete knowledge and 1/3 is completely unaware of the concept and radioprotection actions. Conclusion: The employees of a UH, even at graduated level, need training on radiation protection, because the training course failed in this respect. We believe the same should happen in other health institutions. The actions aimed at training in radiation protection were very well accepted by employees and their effective translation greater individual and collective protection is being evaluated